(untitled) (Journal of Tikapur Multiple Campus, 2015)
Teaching is taken as challenging job throughout the world. It is even more challenging in developing countries like Nepal where it has not developed as a profession very well. Although there are challenges throughout teachers’ career, the frequency and intensity of the problem is very high during the initial phase of career. This paper reports on the nature of challenges faced by beginning teachers in Nepalese schools based on a small scale survey research. Data were drawn from a survey study conducted in the Kathmandu valley. I adopted qualitative method of data collection and analysis. Forty teacher with less than three years of teaching experience and five head-teachers were purposively selected for the study. The study revealed that the beginning teachers face a range of problems and most of them result because of lack of link between what they learn in the colleges/universities and their work places. It was also found that they face various challenges because of lack of preparation and support from different stakeholders.